2017
DOI: 10.6026/97320630013323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling and simulation of three important components of Plant Pathogen Interaction cascade in Vigna mungo

Abstract: Plant pathogen interaction plays a great role in plant immunity. The regulation of various components of plant pathogen interactions is quite complicated and is very important in establishing relationship among components of this system. Yellow Mosaic Disease is common among legumes such as Vigna mungo. Mungbean Yellow Mosaic India Virus (MYMIV) and whitefly (Bemisia tabaci) is a vector causing the disease. Therefore, it is of interest to document the molecule models of three different components of Plant Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the present study, the plant–pathogen interaction pathways in S. davidii seedlings were moderately and severely enriched in DEGs, indicating that the plant–pathogen defence system was rapidly activated. Under abiotic stress, WRKY TFs play an important role in plant transcriptional regulation and pathogen defence ( Singh et al, 2017 ) and have been widely reported in many plant studies ( Pandey et al, 2015 ; Zhang et al, 2018 ). In the present study, the expression of the WRKY33 gene was upregulated under MD and SD stress but did not change significantly under LD stress, indicating that WRKY33 may play a key role in the signal transduction and transcriptional regulation of the S. davidii defence response under MD and SD stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the plant–pathogen interaction pathways in S. davidii seedlings were moderately and severely enriched in DEGs, indicating that the plant–pathogen defence system was rapidly activated. Under abiotic stress, WRKY TFs play an important role in plant transcriptional regulation and pathogen defence ( Singh et al, 2017 ) and have been widely reported in many plant studies ( Pandey et al, 2015 ; Zhang et al, 2018 ). In the present study, the expression of the WRKY33 gene was upregulated under MD and SD stress but did not change significantly under LD stress, indicating that WRKY33 may play a key role in the signal transduction and transcriptional regulation of the S. davidii defence response under MD and SD stress.…”
Section: Discussionmentioning
confidence: 99%